Kebijakan Terhadap Pencegahan Dan Penanganan Kejahatan Pelecehan Seksual Kota Tanjungpinang Tahun 2023 - Aprilia, Dita; Pratama, Rizki Aeva; Halofa, Fatrina; Widiyani, Heni (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2024)
Sexual harassment is behavior that leads to sexual behavior that is unwanted by the victim from the target perpetrator, causing consequences such as feelings of trauma, anger, shame, sadness, etc. Therefore, the aim of this research is to find out what policies for preventing and handling crime in Tanjungpinang City. This research uses a library study method in collecting secondary data. Apart from that, the data collection technique used is descriptive qualitative, by conducting interviews and documentation, the data analysis technique used is summarizing the results of the literature study and interview and then drawing the conclusions. The results obtained from the research are that the government and society and in efforts to prevent and handle sexual crimes, the police and related government work together by providing outreach in the form of education so that sexual crimes do not occur. In this way, policies regarding the solution of cases and the protection of victims can work well.